Mapping Heterotic Loci for Yield and Agronomic Traits Using Chromosome Segment Introgression Lines in Cotton. Issue 8 (11th August 2013) - Guo, Xian; Guo, Yuping; Ma, Jun; Wang, Fang; Sun, Mizhen; Gui, Lijuan; Zhou, Jiajia; Song, Xianliang; Sun, Xuezhen; Zhang, Tianzhen
Abstract In the present study, a set of chromosome segment introgression lines (CSILs) using Gossypium hirsutum L. TM‐1 as the recipient parent and G. barbadense Hai7124 as the donor parent were used to explore the genetic basis of heterosis for interspecific hybrids. Two sets of F1 populations individually derived from CSILs crossing with both parents were configured to investigate heterotic loci (HL) and substitution effect loci (SL). A total of 58 HL and 39 SL were identified in 3 years. One stable HL, hLP‐A4‐3, could be detected in all 3 years. Three HLs, hBS‐A8‐1, hLP‐D6‐1, and hSI‐D7‐11, could be detected in 2 years. Four SLs, sBS‐D7‐1, sLP‐A8‐1, sLP‐D7‐1, and sLP‐D12‐1, could be detected in 2 years. HL and SL tended to be distributed in some HL‐rich chromosome segments with close positions. Compared with QTL detected in a former study, HL showed little overlap with QTL, indicating that trait phenotype and heterosis might be controlled by different sets of loci. All three forms of genetic effects (partial‐, full‐, over‐dominant) were identified, while the over‐dominant effect made the main contribution to heterosis. These results may help lay the foundation for clarifying the heredity mechanism of heterosis in cotton.